2016
DOI: 10.1186/s12974-016-0591-x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous analgesia mediated by CD4+ T lymphocytes is dependent on enkephalins in mice

Abstract: BackgroundT cell-derived opioids play a key role in the control of inflammatory pain. However, the nature of opioids produced by T cells is still matter of debate in mice. Whereas β-endorphin has been found in T lymphocytes by using antibody-based methods, messenger RNA (mRNA) quantification shows mainly mRNA encoding for enkephalins. The objective of the study is to elucidate the nature of T cell-derived opioids responsible for analgesia and clarify discrepancy of the results at the protein and genetic levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 42 publications
(59 reference statements)
3
36
0
Order By: Relevance
“…Transcripts for POMC were undetectable in the colon, whereas previous studies reported positive immunolabeling for beta‐endorphin in human or mouse colonic tissue (Verma‐Gandhu et al., ; Hughes et al., ). This may be caused by differences in experimental conditions including mouse strain and the use of immunohistochemistry rather than RT‐PCR (Basso et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts for POMC were undetectable in the colon, whereas previous studies reported positive immunolabeling for beta‐endorphin in human or mouse colonic tissue (Verma‐Gandhu et al., ; Hughes et al., ). This may be caused by differences in experimental conditions including mouse strain and the use of immunohistochemistry rather than RT‐PCR (Basso et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…23 Data were acquired for each individual sample on 100,000 cells by forward and side scatter intensity on F I G U R E 1 Piroxicam treatment induces (accelerates) colitis in IL-10 −/− mice. Cells were incubated with antibodies in FACS buffer (PBS 1% FCS, 5 mmol/L EDTA, 0.1% NaN 3 ) for 30 minutes on ice.…”
Section: Cytofluorometric Analysismentioning
confidence: 99%
“…After washing, cells were fixed, permeabilized, and then stained with either rabbit anti-Met-enkephalin polyclonal IgG antibodies (Merck-Millipore-Chemicon International) or control rabbit non-immune serum IgG (Jackson Immunoresearch Laboratory, Baltimore, PA) as previously described. 23 Data were acquired for each individual sample on 100,000 cells by forward and side scatter intensity on F I G U R E 1 Piroxicam treatment induces (accelerates) colitis in IL-10 −/− mice. IL-10 −/− mice were fed with standard chow diet without (white symbols) or with piroxicam (black symbols) for 10 d (n = 26 for each group of mice).…”
Section: Cytofluorometric Analysismentioning
confidence: 99%
“…through the arachidonic acid cascade, they also play a role in mediating endogenous peripheral analgesia, as reflected by the increased expression of opioid receptors on the peripheral terminals of sensory neurons and heightened local production of opioid peptides at the site of inflammation (10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). This suggests an integral role of the immune system in mediating analgesia in response to noxious stimuli.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Deletion of genes coding for proenkephalin (PENK) in the brain and immunocytes results in down-regulation of Met-ENK release, suggesting that ENK is synthesised from the same precursor protein molecule in both nervous and immune systems (137). In addition, the production of peripheral opioid peptides involves both circulatory and resident inflammatory cells such as T-and B-lymphocytes, granulocytes (during early inflammation) and monocytes/macrophages (during late inflammation) (16,18,(138)(139)(140)(141).…”
Section: Synthesis and Distribution Of Opioid Peptides In Leukocytesmentioning
confidence: 99%